Pitfalls of electromagnetic tracking in clinical routine using multiple or adjacent sensors - Wegner, Ingmar; Teber, Dogu; Hadaschik, Boris; Pahernik, Sascha; Hohenfellner, Markus; Meinzer, Hans-Peter; Huber, Johannes (The international journal of medical robotics and computer assisted surgery, 2013)
Background While electromagnetic tracking (EMT) holds great promise, there are substantiated concerns about interference within the clinical environment. The purpose of this study was to address accuracy and isolate pitfalls for using multiple or adjacent EMT sensors in clinical routine. Methods A phantom simulating an EMT-guided puncture of the kidney was used to analyse the effects of multiple sensors in the direct vicinity, common clinical environments and the influence of endo-urological instruments. Results No relevant interference due to the investigated instruments was discovered. However, there was a great decrease in accuracy in the vicinity of a C-arm's image intensifier, especially affecting the precision of two adjacent sensors. Conclusion Endo-urological instruments can be safely used for multi-sensor EMT-guided procedures. When avoiding the immediate proximity of the surgical table and the image intensifier, there is a comfortable accuracy corridor. Thus, EMT-assistance is promising for a wide range of procedures if basic conditions are met.
Published online 04 April 2012
Gesehen am 18.10.2021